2021
DOI: 10.3390/coatings11050604
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Biological Activity of Active Films Based on Corn Peptide Incorporated Carboxymethyl Chitosan

Abstract: Active films based on carboxymethyl chitosan incorporated corn peptide were developed, and the effect of the concentration of corn peptide on films was evaluated. Physicochemical properties of the films, including thickness, opacity, moisture content, color, mechanical properties, water vapor permeability, and oil resistance, were measured. Biological activities of the films, including the antioxidant and antibacterial activities, were characterized in terms of 2, 2-diphenyl-1-picrylhydrazyl free radical scave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…For CMCS, peaks around 1585.2 and 1413 cm −1 corresponded to antisymmetric and symmetric stretching vibrations for the -COO-group, respectively [51]. With respect to the FTIR spectra of PVA, the absorption peak at 2936 cm −1 is responsible for the -CH 2 stretching vibration [52].…”
Section: Ft-irmentioning
confidence: 99%
“…For CMCS, peaks around 1585.2 and 1413 cm −1 corresponded to antisymmetric and symmetric stretching vibrations for the -COO-group, respectively [51]. With respect to the FTIR spectra of PVA, the absorption peak at 2936 cm −1 is responsible for the -CH 2 stretching vibration [52].…”
Section: Ft-irmentioning
confidence: 99%
“…CPs have antioxidant activity, are anti-hypertension, and prevent alcohol injury, and have other unparalleled physiological functions [23]. Ma et al found that CPs can effectively reduce the amount of ethanol in the blood after alcoholic intake by plasma alanine and leucine [24].…”
Section: Corn Peptidementioning
confidence: 99%
“…Due to the harmful effects of free radicals on foods, antioxidant activity packaging can remove free radicals and extend the shelf life of foods [26]. The DPPH free radical scavenging activity of bionic chitosan-PBE films are shown in Table 1.…”
Section: Dpph Free Radical Scavenging Activitymentioning
confidence: 99%